Argila montmorilonita modificada com complexos ferro-cyclam e catalisador de Jacobsen como modelo biomimético para oxidação de corantes têxteis - Santos, Synara Maria de Almeida (2019)
Studies show that the biotransformation of azo dyes may be responsible for the formation of amines, benzidines and other intermediates with carcinogenic and mutagenic potential. The formation of these products occurs via oxidation and / or reduction reactions catalyzed by cytochrome P450 (CYP450). However, due to difficulties in working with enzymes, the use of model compounds of CYP450 has been highlighted in studies of catalysis of several substances. The immobilization of these biomimetic catalysts in solid supports is a prominent area because, in addition to preventing the formation of inactive dimers and self- oxidation, it increases the catalytic activity and the selectivity of these reactions allowing the recovery and reuse of these catalysts. Among the various supports used, clays have stood out due to the advantages offered: cost, environmentally friendly and chemically stable. In this study, the biomimetic models of CYP450, cis-diclorocyclamferro (III) chloride (FeCy) and N, N'-bis (3,5-di-tert-butylsalicidene) -1,2-cyclohexanediaminomanganese (III) chloride (JBN) were immobilized on montmorillonite K10 (Mt) and montmorillonite sodium (Mt-Na+) and used to oxidize the orange reactive dye 16 (RL16). The catalysts obtained were quantified by flame atomic absorption spectrometry (FAAS), obtaining the values per support gram of 1.34x10-4 mol g-1 for FeCyMt, 1.93x10-4 mol g-1 for FeCyMt-Na+ and 3.07x10-6 mol g-1 for JBNMt-Na+ and surface area values of 245 m2 g-1 for FeCyMt, 314 m2 g-1 for FeCyMt-Na+ and 255 m2 g-1 for JBNMt-Na+. The Fourier Transform Infrared (FTIR) spectra of the supported materials revealed no changes in the vibrational stretches characteristic of montmorillonite. The images obtained by scanning electron microscopy (SEM) indicated the absence of modification of the surface of the montmorillonite after the immobilization of the catalysts. In the X-ray diffractograms (XRD), using the reflection plane (001), it was possible to observe an increase in the basal distances of montmorillonite after immobilization, thus confirming the presence of the catalysts in the interlamellar region. The thermal stability of the supported materials was verified through thermogravimetric curves. Subsequently, oxidation reactions of the reactive orange dye 16 (RO16) were performed at room temperature, using molar ratio 1: 5: 2500 (catalyst: substrate: oxidant) and quantity of catalyst of 2.0x10-7 for FeCyMt and FeCyMt-Na+ and 5.0x10-8 for JBNMt-Na+, using hydrogen peroxide as oxidant. Oxidation was monitored by UV-Vis molecular spectrophotometry in the time interval from 0 to 1440 minutes, by the disappearance of the absorption band at 492 nm. Oxidation studies were performed in aqueous, acid and basic medium. Reactions in aqueous medium and at pH 6, 8 and 10 showed no changes in the dye spectrum. At pH 2 and 4, the FeCyMt and FeCyMt-Na+ catalysts showed 100% oxidation in a time interval of 480 min for pH 2. For the catalyst JBNMt-Na+ there was 66% oxidation at pH 2. The FeCyMt, FeCyMt-Na+ and JBNMt-Na+ catalysts showed stability and efficiency in the oxidation reactions of the RO16 dye.